Implementation of Merdeka Curriculum by Teachers for Learning Readiness in Madrasah Ibtidaiyah Negeri 11 Blitar - Mutamimah, Kusnul; Rahmawati, Eka Airin; Purwowidodo, Agus (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2025)
Education is a fundamental driver of human development and the foundation of social progress. This research focuses on examining the readiness of teachers to implement the Merdeka Curriculum at Madrasah Ibtidaiyah Negeri (MIN) 11 Blitar. Using a descriptive qualitative method, data were gathered through interviews and classroom observations to obtain comprehensive insights. The results show that teachers have prepared well by designing lesson plans that integrate Learning Objectives, Learning Pathways, and Teaching Modules. Despite these efforts, several obstacles remain, including variations in students’ comprehension levels, limited school facilities, and insufficient teacher experience with the new curriculum. These challenges highlight the need for additional support and professional development. Overall, the study concludes that teachers at MIN 11 Blitar demonstrate promising readiness for implementing the Merdeka Curriculum, but overcoming the identified barriers is essential to achieve a more effective and meaningful learning process for students.